2020
DOI: 10.3390/pathogens9110876
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Mobility of Viral and Host Non-Coding RNAs Reveal Extracellular Vesicles as Intriguing Candidate Antiviral Targets

Abstract: Intercellular communication occurring by cell-to-cell contacts and via secreted messengers trafficked through extracellular vehicles is critical for regulating biological functions of multicellular organisms. Recent research has revealed that non-coding RNAs can be found in extracellular vesicles consistent with a functional importance of these molecular vehicles in virus propagation and suggesting that these essential membrane-bound bodies can be highjacked by viruses to promote disease pathogenesis. Newly em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 125 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…The latest research shows that the amino acid sequences of the SARS-CoV-2 and SARS-CoV RNA-binding domains (RBDs) are highly similar to the predicted protein structures, suggesting that SARS-CoV-2 invades host cells via ACE2 receptor ( 19 , 20 ). A recent study found that the S protein of SARS-CoV-2 strongly interacts with human ACE2 expressed by alveolar epithelial cells and can increase vascular permeability ( 23 ). In addition, the binding affinity of SARS-CoV-2 envelope spikes for the cellular ACE2 receptor is 10-20-fold higher than that of the corresponding structures of SARS-CoV, which may account for the high infectivity of the SARS-CoV-2 in humans ( 24 ).…”
Section: Pathogenesis Of Sars-cov-2mentioning
confidence: 99%
“…The latest research shows that the amino acid sequences of the SARS-CoV-2 and SARS-CoV RNA-binding domains (RBDs) are highly similar to the predicted protein structures, suggesting that SARS-CoV-2 invades host cells via ACE2 receptor ( 19 , 20 ). A recent study found that the S protein of SARS-CoV-2 strongly interacts with human ACE2 expressed by alveolar epithelial cells and can increase vascular permeability ( 23 ). In addition, the binding affinity of SARS-CoV-2 envelope spikes for the cellular ACE2 receptor is 10-20-fold higher than that of the corresponding structures of SARS-CoV, which may account for the high infectivity of the SARS-CoV-2 in humans ( 24 ).…”
Section: Pathogenesis Of Sars-cov-2mentioning
confidence: 99%
“…In silico and bioinformatics assessments revealed several host binding microRNA (miRNA). [56][57][58][59][60][61][62][63] Several host miRNA (15b-5p, 15a-5p, 197-5p, 548c-5p, 548d-5p, 409-3p, 30b-5p and 505-3p) may be involved blocking viral replication. 56,57 Also, viral miRNA is shared with cells miRNA (8066, 5197, 3611, 3934-3p, 1307-3p, 3691-3p, 1468-5p), which may modulate cell response facilitating SARS-CoV-2 infection.…”
Section: Viral Recognition and Cell Metabolismmentioning
confidence: 99%
“…58 Among the different virus escape mechanisms, inhibition of host miRNA maturation, viral miRNA control of the cellular process and metabolic pathways, and viral miRNA sponges are crucial for viral escape. [56][57][58][59][60][61] IFN pathway is inhibited or downregulated, and TGF-β signalling, involved in cell suppression, is enhanced. 49,53,54 The IFN pathway inhibition affects viral RNA recognition by Toll receptors and RIG.…”
Section: Viral Recognition and Cell Metabolismmentioning
confidence: 99%
See 2 more Smart Citations